THE PHOTOGRAPHIC VISUALITY OF ORLANDO DA ROSA FARIA (Editora Impacto Científico, 2025)
This article analyzes the photographic work of visual artist Orlando da Rosa Faria, known as Lando, focusing on the photo book “The Two Sides of the Window”. In this work, the artist uses photography as a means of personal expression, blending experiences from his travels to question the notion of a fixed and stable identity. Through self-representation and simulation, Lando explores the indeterminacy of his own image. In the Conspectus series, the artist establishes a dialogue between photography and painting, challenging the viewer's perception of reality and the appearance of things. His approach expands the boundaries of photographic language by incorporating unconventional framings and monumental images that not only serve rhetorical purposes but also provoke perceptual shifts and demand an imaginative stance from the observer. Lando engages with diverse themes through self-portraits and emotional, physical, and psychic displacements.